Development of IoT-Based Heatstroke Early Symptoms Monitoring System for Students in Malaysia - A Rahim, Nabilah; Othman, Nurmiza (Evolution in Electrical and Electronic Engineering, 2024)
As climate change intensifies, the risk of heat-related illnesses becomes a growing concern, especially for vulnerable populations like young adults. This system aims to proactively address this issue by providing real-time monitoring of early symptoms associated with heatstroke. The system employs a portable device integrated with physiological sensors to detect crucial indicators such as student body temperature, heart rate, and blood oxygen level. Through a user-friendly interface, administrators can access real-time data. The result shows the students' identification alongside the measurement taken from the sensor. The collected data is processed through a sophisticated algorithm that analyzes patterns indicative of heatstroke risk. The data taken from the prototype is being compared to the conventional measurement data and the result is shown in a line graph shown in the result and discussion part. Using the data that has been collected, the data can be transferred to the authorities such as KKM to analyze further about the student’s health condition.